Translating local science fiction as social critique : a case study of Auspicium Melioris Aevi - Lee, Ying Jing (2019)
Although science fiction has traditionally been considered merely as a form of “popular fiction” with little literary value, this genre has gained greater recognition in recent years for its socio-political imagination and speculation of future problems in a postmodern world. In Singapore, sci-fi grew popular with the introduction of Hollywood sci-fi films such as Star Wars and Close Encounters of the Third Kind since the 1970s, and many local writers have sought to create sci-fi pieces reflecting Singapore’s social, political and cultural contexts. However, despite numerous English sci-fi pieces emerging locally in recent years, and the proliferation of popular Chinese sci-fi books such as The Three-Body Problem (San Ti), sci-fi remains a rare genre amongst local Chinese writers. In fact, local Chinese pieces tend to focus on reminiscing Singapore’s cultural past and reflecting on the loss of cultural identity. Translating local sci-fi from English to Chinese is thus an important pathway to promote Chinese sci-fi writing locally; and with the example of Japan and China developing unique cultural styles in SF writing, promotes the creation of a Singapore SF genre relevant to local contexts and social concerns. Using J.Y Yang’s short story Auspicium Melioris Aevi as a case study, the function of sci-fi as a speculative socio-political critique is analysed, and corresponding translation theories to emphasise the nature and significance of sci-fi is discussed. By highlighting major social themes in the story, including criticisms of education and meritocracy in Singapore, the paternalistic style of governance, and the passivity of the general public towards political, social and cultural developments, this case study allows for an exploration in the function of sci-fi in raising socio-political awareness and interpretation into sci-fi references to social realities. Given sci-fi’s critical nature as an operative text-type, this disseration suggests that Newmark’s communicative theory and Jauss’ reception theory are useful guiding principles in sci-fi translation to allow ideas in the source text to be faithfully conveyed to its readers such that its significance as a vessel for social discussion be amplified. The analysis also suggests that sci-fi translation should produced with three major considerations: i) fulfilling its vocative function as socio-political criticism, ii) maintaining aesthetic appeal as a fiction genre, and iii) ensuring naturalness in the translated language to maximise readership. Thus it is recommended that various translation strategies be employed to achieve these translation goals, with the premise that the translator has to fully comprehend the socio-political content implied in the texts before attempting to translate sci-fi texts.